2013
DOI: 10.5901/ajis.2013.v2n3p131
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Values Education and its Connection with Character Education

Abstract: This paper attempts to examine briefly ideas on values education by various academics

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
0
5
0
1
Order By: Relevance
“…Providing personality and character development is another point that teachers consider important regarding values education. In fact, different studies have indicated that values education has impact on the character development of students (Freakley, 2006;Livo, 2003;Sılay, 2013). In addition, teachers thought that values education had a special place in English lessons in terms of raising interest towards the lessons, internalizing the values and ensuring their transformation to behavior, peace, happiness and development of the society, and facilitating the understanding of the universality of values.…”
Section: Results Discussion and Suggestionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Providing personality and character development is another point that teachers consider important regarding values education. In fact, different studies have indicated that values education has impact on the character development of students (Freakley, 2006;Livo, 2003;Sılay, 2013). In addition, teachers thought that values education had a special place in English lessons in terms of raising interest towards the lessons, internalizing the values and ensuring their transformation to behavior, peace, happiness and development of the society, and facilitating the understanding of the universality of values.…”
Section: Results Discussion and Suggestionsmentioning
confidence: 99%
“…Kişilik ve karakter gelişimini sağlaması, öğretmenlerin değerler eğitiminin gerekliliği için önemli gördükleri bir diğer noktayı oluşturmaktadır. Değerler eğitiminin öğrencilerin karakter gelişimleri üzerinde etkisi olduğundan birçok farklı çalışmada da bahsedilmektedir (Freakley, 2006;Livo, 2003;Sılay, 2013). Ayrıca öğretmenler derse karşı ilgiyi artırmasında, değerlerin içselleştirilme-sinde ve davranışa dönmesinin sağlanmasında, toplumun huzuru, mutluluğu ve gelişiminde ve değerlerin evrenselliğinin anlaşılmasının kolaylaşmasında da İngilizce dersinde değerler eğitiminin yeri olduğunu düşünmektedirler.…”
Section: Tartışma Sonuç Ve öNerilerunclassified
“…Increasingly clearer and relevant signals from the education sciences show that additional attention is due to values in the teaching process as well as generally, in school (Harecker, 2012); 3.The increasing width of the moral dimension of the teaching process through which teachers simultaneously perform a double action: a. express their own values and support students in their effort of building their own values and norms. Based on the (implicitly or explicitly) values proposed by teachers, students will gradually turn to practicing the processes of clarifying values and valuation; b. analyse their own values and the values' impact upon their students (Silay, 2013).Studies show that there are few attempts in which teachers are engaged in meta-reflection and dialogue regarding the values that guide their activity (Sunley & Locke, 2010). In this respect, we should not ignore the fact that education as enculturation contributes to harmonizing personal and social interests, making the emotional compatible with the relational from a holistic perspective (Gulati & Pant, 2008).…”
Section: Teachers Values and Values Pedagogymentioning
confidence: 99%
“…In Lebanon (Najah, 2015), recommended reforming character education in public schools. In Rome, Italy (Sölay, 2013), concluded that the mission of higher education is not only science but also character education to help people guarantee a better and moral future.…”
Section: Introductionmentioning
confidence: 99%